Role of Anxiety in Emotional Priming on Dual Mechanism of Control - Kaur, Sehajpreet (My University, 2025)
Cognitive control enables the modulation of action and thought in response to internal objectives, promoting adaptive functioning in complex situations. The Dual Mechanisms of Control (DMC) theory argues that cognitive control is divided into proactive (goal-directed) and reactive (stimulus-driven) modes that help to flexibly mold their actions depending on the requirements of the given task. The current research examines the interaction between the influence of emotional priming (anger, sadness, happiness, and neutral states) and trait anxiety (high and low) on dual mechanisms of control through a spatial Stroop paradigm. Using the State-Trait Anxiety Inventory (STAI) to differentiate anxiety levels and examine the interference effects with varying proportions of congruence to address dual mechanisms of control under varying emotional conditions, this research seeks intervention to address important gaps in cognitive-affective control literature.
Keywords: Dual Mechanisms of Control; Emotional Priming; Trait Anxiety; Spatial Stroop Task; Conflict Adaptation